The views and experiences of disabled children and their siblings : a positive outlook - Connors, Clare, 1957- (Jessica Kingsley Publishers, 2003)
Drawing on one-to-one guided conversations with disabled children and follow-up interviews with their parents and siblings, this volume takes an in-depth look at the effects of disability on disabled children. Approaching this neglected subject through the disabled child's perspective, it considers: disabled children's understanding of disability; the ways in which children negotiate the experience of disability in their everyday lives; children's perceptions of their relationships with professionals and their knowledge and views of service provision; children's aspirations for the future and.